1997
DOI: 10.1097/00001648-199703000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Association among Health Habits, Risk Factors, and All-Cause Mortality in a Black California Population

Abstract: We evaluated dietary and other risk factors in a black California cohort. Baseline data were gathered in 1974 and 1976, and mortality follow-up continued through 1985. A study census questionnaire was returned from 3,299 subjects who lived in a household containing at least one Seventh-Day Adventist. Of these, 1,668 subjects also completed a detailed life-style and dietary questionnaire in 1976. Vital status was ascertained using church records and the California State death tapes. Mortality hazard ratios (HR;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 22 publications
1
55
0
4
Order By: Relevance
“…First, information regarding the shape of the IQ-mortality relation (incremental or threshold) and tests of the existence (or not) of an association in women and ethnic minority groups are required. That a relation between markers of socioeconomic position (including education) and mortality is seen among women (73,74) and ethnic minorities (75) suggests that similar gradients for IQ and mortality would be expected. Second, although all nine studies reported an IQ-all-cause mortality relation, other research suggested that IQ does not relate in the same way to all specific types of morbidity and mortality.…”
Section: Iq and Later Mortality Riskmentioning
confidence: 97%
“…First, information regarding the shape of the IQ-mortality relation (incremental or threshold) and tests of the existence (or not) of an association in women and ethnic minority groups are required. That a relation between markers of socioeconomic position (including education) and mortality is seen among women (73,74) and ethnic minorities (75) suggests that similar gradients for IQ and mortality would be expected. Second, although all nine studies reported an IQ-all-cause mortality relation, other research suggested that IQ does not relate in the same way to all specific types of morbidity and mortality.…”
Section: Iq and Later Mortality Riskmentioning
confidence: 97%
“…These studies, however, are inconclusive because they often lack appropriate adjustments for confounding (eg, confounding by age because obese persons are generally 7 years younger at time of their first MI than normal-weight individuals), but they stress the need for high-quality additional research. Finally, population-based cohort studies that study all-causes mortality in relation to the intake of fruits and vegetables, [87][88][89][90] whole grains, 87,91,92 legumes, 93 nuts, 94,95 or salt 96 -98 are scarce but are generally supportive of a protective effect of the recommendations.…”
Section: Regular Fish (Oil) Consumptionmentioning
confidence: 99%
“…Diversos estudos 16,17 vêm indicando que seu consumo freqüente está associado a risco reduzido de doenças coronarianas. Ainda que 73 a 95% de suas calorias sejam provenientes dos lipídios, eles são pobres em gorduras saturadas, sendo 60% das calorias compostas por ácidos graxos monoinsaturados, o que auxilia a redução do colesterol total e da LDL-c, sem, no entanto, reduzir a HDL-c 18 .…”
Section: Fatores Dietéticos Importantes Nas DCVunclassified